2018
DOI: 10.1038/s41598-018-23692-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intestinal Microbiota on Brain Development in Humanized Gnotobiotic Mice

Abstract: Poor growth in the Neonatal Intensive Care Unit is associated with an increased risk for poor neurodevelopmental outcomes for preterm infants, however the mechanism is unclear. The microbiome has increasingly been recognized as a modifiable environmental factor to influence host development. Here we explore the hypothesis that the microbiome influences both growth phenotype and brain development. A germ free mouse transfaunation model was used to examine the effects of preterm infant microbiotas known to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 91 publications
1
101
1
2
Order By: Relevance
“…[70,71] On the other hand, the microbiota of Hydra shows a remarkable dynamics during ontogenesis. [73,74] Finally, our recent data suggest that the transcriptional factor FoxO serves as an intracellular hubprotein, and controls both bacterial colonization and stem cell activity in Hydra. Strikingly, these shifts correlate with changes in the nerve cell density during the ontogeny of Hydra.…”
Section: How Does the Microbiota Affect Development?mentioning
confidence: 99%
“…[70,71] On the other hand, the microbiota of Hydra shows a remarkable dynamics during ontogenesis. [73,74] Finally, our recent data suggest that the transcriptional factor FoxO serves as an intracellular hubprotein, and controls both bacterial colonization and stem cell activity in Hydra. Strikingly, these shifts correlate with changes in the nerve cell density during the ontogeny of Hydra.…”
Section: How Does the Microbiota Affect Development?mentioning
confidence: 99%
“…Gut microbiota can elicit signals to the brain and vice versa via the vagal nerve system. SFCAs may have a direct effect on brain function and development [3, 58, 59]. …”
Section: Neurodevelopment In Survivors Of Necmentioning
confidence: 99%
“…To specifically study the impact of preterm infant dysbiosis on neuroinflammation, we used a fecal transfaunation model. We demonstrated that the microbiota of a preterm infant associated with a poor growth phenotype when transfaunated to germ‐free (GF) pregnant mice was associated with both systemic inflammation and neuroinflammation in the pups as evidenced by elevated pro‐inflammatory mediators including IL‐1β, TNF, and IFNγ in the circulation and increased NOS1 in the brain (Lu et al, ). Emerging studies using whole microbial communities associated with a phenotype instead of a single bacterial product, that is, a cytokine or a bacterial component, shed new light on how dysbiosis of the gut microbiota impacts neurological development, raising the possibility of whole microbiota manipulation as a therapeutic target.…”
Section: Contribution Of Dysbiosis In Preterm Infants To Neuroinflammmentioning
confidence: 99%
“…One approach to model the early effects on newborn development is to colonize GF pregnant dams with specific microbial communities and evaluate the offspring neurodevelopment. Using this model, we have demonstrated that maternal colonization with microbiota from a poor growth human infant resulted in altered neuronal development evidenced by decreased expression of the neuronal development marker NeuN and an altered myelination process evidenced by reduced expression of the myelination marker myelin basic protein at both preweaned and immediate postweaned ages of the offspring (Lu et al, ). The preterm infant microbiota effects on brain development were mediated by local and systemic IGF‐1 levels and neuroinflammation.…”
Section: Emerging Pathways Connecting Microbiome and Brain Developmentmentioning
confidence: 99%
See 1 more Smart Citation